Enhancing household iodized salt practices through contextual health education: An intervention study in rural Jeneponto, Indonesia - Alam, Syamsul; Rahmah, Nur; Arranury, Zilfadhilah; Fauzan, Ahmad; Meliyanti, Nur; Febriayu, Dwi; Ardiansyah, Ardiansyah (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2025)
Iodine deficiency remains a significant nutritional issue in Indonesia, particularly affecting rural communities with limited access to accurate health information. This research-based community engagement aimed to evaluate the effectiveness of an educational intervention on household knowledge and practices related to iodized salt usage in Bontobakka Hamlet, Jeneponto Regency. The intervention employed a door-to-door campaign using poster media and involved 31 female respondents who were assessed at three time points: pre-intervention, post-intervention, and six months post-intervention. The study utilized a summative evaluative approach based on the CIPP model (Context, Input, Process, Product) to measure program impact. The Friedman test revealed a statistically significant improvement in knowledge levels (p = 0.028), with 87.1% of participants achieving a